Redefining vascular repair: revealing cellular responses on PEUU—gelatin electrospun vascular grafts for endothelialization and immune responses on in vitro models - Rodríguez-Soto, María A.; Riveros-Cortés, Alejandra; Orjuela-Garzón, Ian C.; Fernández-Calderón, Inés María; Rodríguez, Cristian F.; Vargas, Natalia Suárez; Ostos, Carlos; Camargo, Carolina Muñoz; Cruz, Juan C.; Kim, Seungil; D’Amore, Antonio; Wagner, William R.; et al. (Frontiers in Bioengineering and Biotechnology, 2024)
Tissue-engineered vascular grafts (TEVGs) poised for regenerative applications are central to effective vascular repair, with their efficacy being significantly influenced by scaffold architecture and the strategic distribution of bioactive molecules either embedded within the scaffold or elicited from responsive tissues. Despite substantial advancements over recent decades, a thorough understanding of the critical cellular dynamics for clinical success remains to be fully elucidated. Graft failure, often ascribed to thrombogenesis, intimal hyperplasia, or calcification, is predominantly linked to improperly modulated inflammatory reactions. The orchestrated behavior of repopulating cells is crucial for both initial endothelialization and the subsequent differentiation i of vascular wall stem cells into functional phenotypes. This necessitates the TEVG to provide an optimal milieu wherein immune cells can promote early angiogenesis and cell recruitment, all while averting persistent inflammation. In this study, we present an innovative TEVG designed to enhance cellular responses by integrating a physicochemical gradient through a multilayered structure utilizing synthetic (poly (ester urethane urea), PEUU) and natural polymers (Gelatin B), thereby modulating inflammatory reactions. The luminal surface is functionalized with a four-arm polyethylene glycol (P4A) to mitigate thrombogenesis, while the incorporation of adhesive peptides (RGD/SV) fosters the adhesion and maturation of functional endothelial cells. The resultant multilayered TEVG, with a diameter of 3.0 cm and a length of 11 cm, exhibits differential porosity along its layers and mechanical properties commensurate with those of native porcine carotid arteries. Analyses indicate Con formato: Inglés (Estados Unidos)high biocompatibility and low thrombogenicity while enabling luminal endothelialization and functional phenotypic behavior, thus limiting inflammation in in-vitro models. The vascular wall demonstrated low immunogenicity with an initial acute inflammatory phase, transitioning towards a pro-regenerative M2 macrophage-predominant phase. These findings underscore the potential of the designed TEVG in inducing favorable immunomodulatory and pro-regenerative environments, thus holding promise for future clinical applications in vascular tissue engineering.